2020
DOI: 10.1016/j.immuni.2020.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-8 and FADD: Where Cell Death and Inflammation Collide

Abstract: Caspase-8 is a master regulator of cell death pathways, although its regulation during inflammation remains elusive. Using elegant mouse genetic approaches, Schwarzer et al. and Tummers et al. revealed the importance of FADD in regulating caspase-8-mediated inflammatory responses and gut homeostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Post-mortem lung sections has revealed that pulmonary inflammatory responses may induce infiltration of inflammatory cells that trigger strong immune pathogenesis ( Li et al, 2020 ). Mechanisms of inflammatory response and cell death are strongly linked during SARS-CoV-2 infection ( Amaral and Bortoluci, 2020 ). The infection of lung cells activates caspase-8 to trigger cell death pathways, where apoptosis, pyroptosis, and necroptosis are involved.…”
Section: Discussionmentioning
confidence: 99%
“…Post-mortem lung sections has revealed that pulmonary inflammatory responses may induce infiltration of inflammatory cells that trigger strong immune pathogenesis ( Li et al, 2020 ). Mechanisms of inflammatory response and cell death are strongly linked during SARS-CoV-2 infection ( Amaral and Bortoluci, 2020 ). The infection of lung cells activates caspase-8 to trigger cell death pathways, where apoptosis, pyroptosis, and necroptosis are involved.…”
Section: Discussionmentioning
confidence: 99%
“…Although the conventional idea that inflammatory caspase activation would be protective by enhancing immunity against SARS-CoV-2 through the removal of infected cells and recruitment of monocytes to injury sites, concomitant pyroptosis exacerbating inflammation due to cellular release of DAMPs could lead to tissue death, organ failure, and septic shock (70,71). While caspase-8 is known predominately as a mediator of apoptosis, it is also a master regulator of pyroptosis and necroptosis (72) and is capable of processing pro-IL-1b and pro-IL-18 into their functional cytokine forms (73)(74)(75). Caspase-8 can regulate necroptosis, unregulated cell death, by preventing the phosphorylation of MLKL into its active form, phospho-MLKL, by inactivating RIPK1 and RIPK3 by proteolytic cleavage (76)(77)(78).…”
Section: Caspase-mediated Inflammation and Pyroptosismentioning
confidence: 99%
“…Caspase-8, which was previously viewed exclusively as an apoptotic caspase, has now emerged as a master regulator of the three major cell death pathways, including apoptosis, pyroptosis, and necroptosis. 7 Recently, it was reported that caspase-8 can induce the expression of pro-inflammatory cytokines and process pro-IL-1β and IL-18 in the same way as caspase-1, resulting in the release of bioactive cytokines, through either pyroptosis or necroptosis. 8 The role of caspase-8 in mediating inflammatory responses has been reported in the context of infection with fungal pathogens such as Candida albicans and Aspergillus fumigatus.…”
Section: Introductionmentioning
confidence: 99%